Documento de consenso sobre nuevas terapias para retrasar la progresión de la enfermedad renal crónica con énfasis en los iSGLT-2: implicaciones para Latinoamérica (2024)
Chronic kidney disease (CKD) is a health problem worldwide and in Latin America (LA), which comprises 20 countries with a population of more than 620 million inhabitants, with great demographic, economic and health heterogeneity. The prevalence of CKD in LA is higher than worldwide, although it varies within the region. The main cause of CKD is diabetes mellitus, although in some countries, especially in Central America, there is a high prevalence of CKD of non-traditional causes (Mesoamerican nephropathy). The main modality of replacement therapy is hemodialysis. The burden of CKD is very high, with great variation among LA countries with respect to public policies. Recently, there has been a very important advance in nephroprotective interventions, such as sodium-glucose transporter type 2 inhibitors. In this consensus, we present an evidence-based review of their indications in patients with CKD (diabetic and non-diabetic), proposing recommendations for their use, and describing the barriers for their implementation in LA. We conclude that prevention and early management of CKD should be promoted, which can be cost-effective to substantially mitigate the magnitude of the problem.